1998
DOI: 10.1002/pc.10118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term ultraviolet light irradiation on polymer matrix composites

Abstract: This study reports the individual and combined effects of ultraviolet light and thermal shock on the physical properties of polymer matrix composites in air and in a "near-vacuum system." The longest exposure time was 180 days. It was found that the weight loss of composites increased with irradiation time. In the graphite/epoxy system, the weight loss in air was 2-3 times that in a "near-vacuum system." Similarly, the weight loss of the glass/epoxy system in air was 3-6 times that in a "near-vacuum system." T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…The DC reached 98% after three layers was added, and then kept a certain value. This suggested that the exposure dose should be controlled during curing process for every layer to pretend composite from over‐curing which would result in decrease of mechanics 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DC reached 98% after three layers was added, and then kept a certain value. This suggested that the exposure dose should be controlled during curing process for every layer to pretend composite from over‐curing which would result in decrease of mechanics 21…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the exposure dose should be controlled during curing process for every layer to pretend composite from over-curing which would result in decrease of mechanics. 21 The effect of exposure dose on ILSS Like the effect of temperature on performance of composites in a thermal cure, UV exposure dose has a significant effect on the performance of UV curable composites. Figures 4 and 5 show the correlation between ILSS and UV exposure dose, ILSS and DC, respectively.…”
Section: Transmission Character Of Composite Layermentioning
confidence: 99%
“…This alters the chemical structure by molecular chain scission or chain crosslinking and results in material deterioration (Ranby and Rabek 1975). For prolonged exposure to UV radiation, the matrix dominated properties, such as interlaminar shear strength, flexural strength, and flexural stiffness can suffer severe deterioration (Chin et al 1997;Liau and Tseng 1998;Shin et al 2000a, b;Kumar et al 2002;Signor et al 2003). Furthermore, degradation phenomena due to UV radiation and moisture when acting together can significantly accelerate the degradation process of the matrix.…”
Section: Typical Aerospace Composites and Their Environmental Performmentioning
confidence: 99%
“…Temperature Creep/relaxation effects Gramoll et al (1990), Greenwood (1975), Hugo et al (1993), Panasyuk et al (1987) 10 Moisture Panasyuk et al (1987) 11 Loading cycle Ando et al (1997), Machida (1997) Loading cycle Mahfuz et al (2000), Datta et al (2002), Dzenis (2003), Karbhari et al (2003) 15 Temperature Liau and Tseng (1998), Steckel et al (1999), Kumar et al (2002) 16 Moisture UV exposure effect Steckel et al (1999), Busel and Lockwood (2000), Karbhari et al (2003), Kumar et al (2002) 17 Freeze and thaw Liau and Tseng (1998) 18 UV light Chin et al (1997), Liau and Tseng (1998), Kumar et al (2002) , Signor et al(2003) 19 Temperature Fire effects Busel and Lockwood (2000), Balázs and Borosnyói (2001), Mouritz (2002), Mouritz (2003), Sorathia et al (1993), Sorathia et al (1996), Mourtiz and Mathys (1999), Mourtiz and Mathys (2001), Mourtiz (2003) 20 Fire attack because of editorial constraints. For detailed information on the seven DMs, refer to Hong (2005).…”
Section: Damage Modes For Frp Bridge Deck Panelsmentioning
confidence: 99%
“…For example, to determine the intensity of EFs, 'Temperature' for the city of West Lafayette, Indiana, the threshold level for temperature was assumed to be ≤4 • C (40 • F) and ≥20 • C (68 • F) when it could influence certain DMs. The limited range of temperature was determined according to the experimental conditions used by previous research projects related to the EF 'temperature' (Greenwood 1975, Watanabe 1979, Panasyuk et al 1987, Gramoll et al 1990, Dutta 1992, Hugo et al 1993, Bank et al 1995, Dutta and Hui 1996, Chin et al 1997, Liau and Tseng 1998, Steckel et al 1999, Haramis et al 2000, McBagonluri et al 2000, Datta et al 2002Karbhari et al 2002, Kumar et al 2002 …”
Section: Intensity Of Efsmentioning
confidence: 99%